Students’ and examiners’ perception of feedback practices following OSCE in Uniport - Abinye, Alex-Hart, Balafama; Olabisi, Arigbede Abiodun; Tudor, Chinnah (Asian Journal of Education and Training, 2023)
The Objective Structured Clinical Examination (OSCE) offers several opportunities for effective feedback to be given to students to improve their performance. This study aimed to evaluate the feedback practices following OSCE in the University of Port Harcourt (Uniport). This was descriptive research involving the administration of semi-structured questionnaires to examiners in the Faculty of Clinical Sciences and final year medical students in Uniport. Information sought centred on their perception of feedback practices following OSCE. Data was analysed using descriptive statistics and Chi-square. The result showed that 114 examiners participated in the study. There were 72 (63.16%) male and 42 (36.84%) female examiners with male to female ratio of 1.7:1. Ninety students participated in the study. There were 49 (54.44%) males and 41 (45.56%) females. Their mean age was 25.42±2.36. There were significant differences between the examiners and students perception of feedback practices following OSCE in Uniport in terms of whether (P=0.009) and when (P=0.0014) it is provided. Majority of the examiners (58.49%) and almost all the students (91.49%) reported that feedback resulted in improved performance. The stud y showed that about half of the students claimed that feedback is given following OSCE in Uniport. Feedback practice following OSCE in Uniport is satisfactory in some aspects and deficient in some other aspects. Incorporate quality feedback practices into the OSCE process in all medical schools will improve skills development and learning.